Analisis Hasil Quality Control Pemeriksaan Profil Lipid di Laboratorium Rumah Sakit Umum Daerah Wonosari - Miftakhul Jannah, Hasnida; Aji Bagus Widyantara; Yeni Rahmawati (CV. CENDIKIA JENIUS INDONESIA, 2024)
Clinical laboratory is a health examination laboratory that carries out examination services to obtain health information, especially to support efforts to diagnose and restore health. Clinical laboratories need to be organized in a quality manner to support efforts to improve the quality of public health. The research design used is descriptive analytical. The purpose of this study was to determine the accuracy, precision and evaluation of the Levey Jenning chart with the Westgard rule. This study was conducted in the laboratory of the Wonosari Regional General Hospital by taking secondary data in October-December 2023 which was then processed using the Levey Jenning chart and the Westgard rule. The results showed good/high accuracy in the parameters of cholesterol, triglycerides, HDL and LDL while some precision was outside the specified range. Evaluation of the Levey Jenning chart obtained the rule, namely the warning rule. The conclusion of the examination of the precision of the cholesterol, triglycerides, LDL parameters was high, the accuracy of the examination was high and the evaluation results were subject to the rule, namely the warning rule. It is recommended that the Wonosari Regional General Hospital Laboratory continue to maintain and improve the accuracy and precision of examinations by paying more attention to control materials.